Taking clinical psychology postgraduate training into the next decade : aligning competencies to the curriculum : final report. - Pachana, Nancy; Sofronoff, Kate; Baillie, Andrew; Halford, Kim; Helmes, Edward; Murray, Gregory; O’Donovan, Annalise (Australian Learning and Teaching Council, 2011)
Report from a research project into better aligning competencies and the Australian curriculum in clinical psychology with best practice for new postgraduates, so that they are prepared to function in the current and future health service climate. We are developing and where feasible, trialing training innovations to both extend the evidence base for best practice in clinical psychology training. These revisions to the curriculum are designed to be flexible and responsive to new initiatives, such as the continuing changes to Medicare access for psychological treatment. This challenge can only be met through a national cooperative effort involving key stakeholders: the national registration board, professional peak bodies, and major university training programmes. [Executive summary]